Criminal justice act 2003: (2) Criminal justice reform: Principles, human rights and public protection - Ashworth, A (2004)
This article scrutinises the notion of public protection that is said to underlie many of the recent criminal justice reforms, most particularly the Criminal Justice Act 2003. It is argued that many current policies are not supported either by principle or by evidence of effectiveness.